Implementation of an International Vessel Wall MR Plaque Imaging Research Network: Experience with the ChAMPION Study - Yannan Yu; Wei-Hai Xu; Arindam Rano Chatterjee; Todd LeMatty; Meng Yao; Ming-Li Li; Truman Brown; Maria Vittoria Spampinato; Renee Martin; Marc I. Chimowitz; Colin Derdeyn; Tanya N. Turan (Clinical and Translational Neuroscience, 2022)
Background and Objective: Intracranial atherosclerosis (ICAS) is one of the most common causes of stroke worldwide. High-resolution Vessel Wall MR imaging (VW-MR) is commonly used to study ICAS, but in order to accelerate advances in the field of VW-MR ICAS research, the establishment of a multicenter research network is needed. We introduce our experience in establishing a collaborative international VW-MR ICAS research network in China and North America using an innovative, disease-specific ICAS imaging phantom for standardization of VW-MR sequences at the sites. Methods: Both the Medical University of South Carolina and Peking Union Medical College functioned as Central Coordinating Centers in the network. PUMC identified research centers within China that had the potential for collaboration on VW-MR ICAS research based on networking and prior experience. All selected centers refined MRI sequences using an ICAS phantom with study principal investigators virtually present in real-time during scanning. MRI sequences were efficiently calibrated utilizing the broad expertise of all members of the research team. All centers further validated MRI sequences with human subjects. Results: We identified 11 Chinese hospitals as the potential collaborating sites for the network. Of the 11 selected sites, six sites were able to complete the required VW-MR scanning and sequence refinement using the ICAS phantom and subsequent human subjects. Conclusion: The study demonstrated the feasibility of establishing a cross-continent collaborative VW-MR research network and the use of a disease-specific phantom to facilitate convenient and efficient sequence modification for image quality standardization, which is needed for future multicenter VW-MR studies.